Total knee arthroplasty in a patient with ipsilateral hip ankylosis: A case report. Issue 36 (September 2019) - Tang, XianZhe; Yan, ZuYun; Wang, Wanchun; Liu, Tang
Abstract: Rationale: There is a large number of people that have knee degeneration in China. Total knee arthroplasty is one of the most effective methods of treatment in the later stages of the disease. However, there are challenges when performing total knee arthroplasty on patients with ipsilateral hip akylosis. So far, there are few reports on postoperative curative effect of total knee arthroplasty for these patients. This case report records how to perform total knee arthroplasty in a patient with ipsilateral hip ankylosis. Patient concerns: Due to ankylosing spondylitis, the flexion of the patient's hips are restricted in 10°, which leads to a limited ipsilateral knee flexion to 30° when she is in the supine position. Diagnoses: Right knee osteoarthritis; right hip ankylosis. Interventions: We modified the traditional surgical position to allow easy exposure of the knee during surgery. After total knee arthroplasty, the patient was included in a planned training program, and was followed for 6 months. Outcomes: The patient walked well without ambulation aid and achieved satisfactory knee joint function. Lessons: Conversion of a fused hip to a total hip arthroplasty does improve the quality of life of patients, but, given the high incidence of complications and more financial burden to the patient, we modified traditional surgical position of the patient to provide ideal surgical exposure of the knee. We hope that this case can be used as a reference for clinicians to deal with similar situations.